Mapping Metacognitive Levels of Students in Solving Gender-Based Inheritance Problems - Tasya Novian Indah Sari (Postgraduate, University of Mataram, 2023)
Metacognition ability has a strategic role in solving problems in learning, one of which is solving the problem of genetic inheritance. The aim of the study was to determine the metacognitive level in solving the problem of inheritance of class IX students based on gender. The quantitative descriptive research method was carried out at SMPN 1 Bendo December 2022-January 2023. The research population was 239 class IX students. The research sample was 239 class IX students using saturated sampling technique. Research instrument with metacognitive level essay questions in solving valid and reliable inheritance problems. Quantitative descriptive data analysis technique and one way ANOVA. The results showed that the highest percentage of male and female students' metacognitive levels was at the strategic use level and the lowest was at the reflective use level. Tacit use metacognitive level, the highest percentage of male students 27% and 22% of female students. The metacognitive level of aware use has the highest percentage of male students 21% and 20% female. Strategic use metacognitive level, highest percentage of male students 38% and lowest is female students, 42%. The highest percentage of metacognitive reflective use is 15% of male students and 15% of female students. The results of the one-way ANOVA test with an alpha of 5% showed no difference in metacognitive level in solving problems of inheritance based on the gender of male and female students.